Performance of White Clover-Grasses Mixtures: Part-II Nitrogen Fixation and Transfer from White Clover to Associates Grasses - IBRAHIM ERKOVAN, H.; TAN, MUSTAFA; BASRI HALITLIGIL, M.; KISLAL, HAKAN (Asian Journal of Chemistry, 2010)
This research was made to investigate fixation and transfer of white clover-grass mixtures. Among legumes, white clover (Trifolium repens L.) and grass plants, smooth bromegrass (Bromus inermis Leyss.), red fescue (Festuca rubra L.) and O. grass (Dactylis glomerata L.) were tested in binary mixtures. According to two year-average results, nitrogen fixation in the pure sowing of white clover was higher. On the other hand, in mixtures, the fixation amount has been higher in which the legume rate was high. The nitrogen transfer from legume to grass changed between 37.67 % in white clover-O. grass and 44.04 % in white clover- smooth bromegrass mixtures. Amount of residual N from fertilizer in soil was decreased while grass ratio was increased.